Gcn5-Related N-Acetyltransferases (GNATs) With a Catalytic Serine Residue Can Play Ping-Pong Too - Baumgartner, Jackson T.; Habeeb Mohammad, Thahani S.; Czub, Mateusz P.; Majorek, Karolina A.; Arolli, Xhulio; Variot, Cillian; Anonick, Madison; Minor, Wladek; Ballicora, Miguel A.; Becker, Daniel P.; Kuhn, Misty L. (Frontiers in Molecular Biosciences, 2021)
Enzymes in the Gcn5-related N-acetyltransferase (GNAT) superfamily are widespread and critically involved in multiple cellular processes ranging from antibiotic resistance to histone modification. While acetyl transfer is the most widely catalyzed reaction, recent studies have revealed that these enzymes are also capable of performing succinylation, condensation, decarboxylation, and methylcarbamoylation reactions. The canonical chemical mechanism attributed to GNATs is a general acid/base mechanism; however, mounting evidence has cast doubt on the applicability of this mechanism to all GNATs. This study shows that the Pseudomonas aeruginosa PA3944 enzyme uses a nucleophilic serine residue and a hybrid ping-pong mechanism for catalysis instead of a general acid/base mechanism. To simplify this enzyme’s kinetic characterization, we synthesized a polymyxin substrate analog and performed molecular docking experiments. We performed site-directed mutagenesis of key active site residues (S148 and E102) and determined the structure of the E102A mutant. We found the serine residue is essential for catalysis toward the synthetic substrate analog and polymyxin B, but the glutamate residue is more likely important for substrate recognition or stabilization. Our results challenge the current paradigm of GNAT mechanisms and show that this common enzyme scaffold utilizes different active site residues to accomplish a diversity of catalytic reactions.